Tiktok Shop Sebagai Teknologi Pemasaran dan Penjualan Digital Untuk UMKM - Surachman, Adhie; Darmawan, Arief; Tresnawati, Amilia (Coopetition : Jurnal Ilmiah Manajemen, 2025)
The development of digital communication technology used in business has enabled marketing or sales as a form of digital economy that no longer requires face-to-face meetings. The growth of Indonesia's digital economy is largely supported by the e-commerce sector, which is around 34% or equivalent to IDR 1,900 trillion in 2030. As the digital economy grows, the penetration of Internet users in Indonesia is also increasing. The "Digital 2023" report shows that in early 2022, Indonesian Internet users reached 204.7 million. TikTok Shop has become an increasingly popular digital economy platform for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in the past five years. This study uses a literature review method with a descriptive approach. The results of the study show that Tiktok Shop provides e-commerce features that are useful and easy to use by MSMEs. Likewise, transactions that can be carried out from the same platform allow buyers and sellers to communicate easily before making transactions. Including various features in creating content that supports MSMEs to promote products, sales streaming videos, building followers, and creating events that invite potential buyers. Keywords: Tiktok Shop, Digital Technology, Marketing and Selling, SMEs.